Chartreuse d’Ema as an archetype of modern mass housing - Zavadovsky, Petr (project baikal, 2026)
The article examines an important historical prototype for Le Corbusier’s work – the Carthusian monastery in Galuzzo. It also analyzes the formal and symbolic influence of the monastery’s architecture on the formation of the conceptual foundations of Le Corbusier’s residential architecture, as well as the reproduction of the characteristic features of the monastery’s architecture in the Immeuble-villas project
Keywords: Le Corbusier; dwelling; the Carthusian monastery; Ema